Estimating the Cost of Executive Stock Options: Evidence from Switzerland - Wolfgang Drobetz; Pascal Pensa; Markus M. Schmid (University of Basel, Center of Business and Economics (WWZ), 2007)
It is often argued that Black-Scholes (1973) values overstate the subjective value of stock options granted to risk-averse and under-diversified executives. We construct a “representative” Swiss executive and extend the certainty- equivalence approach presented by Hall and Murphy (2002) to assess the value-cost wedge of executive stock options. Even with low coefficients of relative risk aversion, the discount can be above 50% compared to the Black-Scholes values. Regression analysis reveals that the equilibrium level of executive compensation is explained by economic determinant variables such as firm size and growth opportunities, whereas the managers' pay-forperformance sensitivity remains largely unexplained. Firms with larger boards of directors pay higher wages, indicating potentially unresolved agency conflicts. We reject the hypothesis that cross-sectional differences in the amount of executive pay vanish when risk-adjusted values are used as the dependent variable.
Keywords: J33; G13; G32; 330; Managerial compensation; incentives; executive stock options; option valuation; risk aversion; Aktienoption; Führungskräfte; Leistungsanreiz; Risikoaversion; Black-Scholes-Modell; Schweiz